Epigenetic changes of DRD2 gene in pathogenesis of schizophrenia - Abd. Rahim, Nour El Huda; Rahim, Mohd Nabil Fikri; Ku Zaifah, Norsidah; Mohd Noor, Hanisah; Abdullah, Kartini; A. Talib, Norlelawati (Kulliyyah of Medicine, International Islamic University Malaysia, 2017)
Introduction: The dopamine hypothesis has earlier dominated the theories for the development of schizophrenia based on the early pharmacologic evidence. The antipsychotic drugs, among others, is thought to interfere with the function of the dopamine D2 receptor (DRD2) resulting in clinical improvement. Accumulating evidence suggest the role of epigenetic mechanisms in the pathophysiology of schizophrenia. Despite this, specific evidence linking the DRD2 DNA methylation with schizophrenia is insufficient mainly due to the poor accessibility and limited brain samples. Of late, new data has suggested the global impact of DNA methylation in the development of schizophrenia, thus methylation in the peripheral blood could infer changes in the brain. Therefore, the aim of the study is to assess the DRD2 DNA methylation in the peripheral blood of schizophrenia.